The material composition of the core material of Nizhny Kenzhasai area (Almalyk ore region) - Kushakov Abdulla; Kushakov Fayzulla; Romanov Sayfulla; Togaev Isomiddin; Khusainov Khurshid; Akmalov Shamshodbek; Ibragimova Zaytuna (BIO Web of Conferences)
This study investigates the material composition of core samples obtained from the Nizhny Kenzhasai area, located within the central tectonic block of the Almalyk ore region. The primary objective is to determine the petrographic, mineralogical, and geochemical characteristics of ore-bearing rocks in relation to gold-silver mineralization. Core samples were collected from drilled wells with continuous sampling. Microscopic petrographic analysis was performed to examine the structural and textural features of the rocks, while spectral analysis was used to quantify the concentrations of major and trace elements, including Fe, Cu, Ag, As, Pb, and Zn. The results indicate elevated contents of gold and silver in altered andesitic porphyrites, metasomatic rocks, and andesitic porphyrite tuffs. Notably, chalcopyrite-and arsenopyrite-bearing zones show a high concentration of ore minerals. Two distinct gold-silver ore-bearing horizons were identified within the Akcha Formation: one located at the lower contact with Devonian-Carboniferous limestones, and the other in the middle part of the formation within pyritized and altered andesitic porphyrites. The identification of these ore horizons highlights the significant economic and geological potential of the Nizhny Kenzhasai area.